Developing Introverted and Extroverted Students’ Descriptive Writing through Kalesang Values and FRESH Technique - Natalia Manuhutu; Rudi Hartono; Abdurrachman Faridi; Zulfa Sakhiyya (Jurnal Pemberdayaan Masyarakat, 2025)
This study examines the role of Maluku local wisdom, specifically "Kalesang" values, in enhancing students' descriptive writing competence through the FRESH technique among introverted and extroverted learners. This research aims to develop a culturally responsive and personality-sensitive pedagogy that integrates linguistic skills, cultural identity, and individual learning styles. Hence, this qualitative case study enlisted eight ninth-grade students from a junior high school in Masohi, Maluku, Indonesia. The data were collected through students’ writing products, in-depth interviews, and classroom observations. Afterward, the data were analyzed using a thematic analysis through the theoretical lens of sociocultural theory, differentiated instruction, and multiple intelligences theory. The results indicate that combining structured writing strategies with local values enhances coherence and elaboration in student texts, while also deepening cultural awareness and learner motivation. This study contributes to language education research by offering a replicable model for integrating indigenous knowledge with evidence-based pedagogy, promoting inclusive and meaningful learning in diverse EFL classrooms.